Prospective evaluation of early local complications of stoma and their risk factors - Jana, Koustav; Bera, Pritin; Mukhopadhyay, Arunima; Bhattacharya, Ujjwal (International Surgery Journal, 2020)
Background: Bowel stoma namely ileostomy and colostomy are frequently performed procedure and often associated with complications. Aim of this study was to assess early local complications and association with any risk factors. Methods: A total of 99 patients undergoing ileostomy or colostomy were analysed prospectively over a period 18 months. Comorbidity, preoperative clinical data, operative time, local complications within 12 weeks and hospital stay were documented. Univariate and multivariate analysis were used to find out any association. Results: Sixty-four ileostomies and 35 colostomies were analysed in our study. Median age was 55 years in both groups. Nontraumatic bowel perforation (42%) and colorectal malignancy (48.6%) were most common etiology for ileostomy and colostomy formation respectively. 64% of ileostomy and 68% of colostomy had one or more complications. Skin excoriation (31%) was most common complication in ileostomy group and it was stomal prolapse (17%) in colostomy group. Poor stoma care was prevalent in both groups. We found diabetes to have significant association with skin excoriation (p=0.002). Conclusions: Diabetes was identified as significant risk factor for skin excoriation in ileostomy group. Further long term data and larger population are needed for better evaluation of stomal complication and their risk factors.